2020
DOI: 10.1101/2020.07.12.20151316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pericarditis and myocarditis long after SARS-CoV-2 infection: a cross-sectional descriptive study in health-care workers

Abstract: Background: Cardiac sequelae of past SARS-CoV-2 infection are still poorly documented. We conducted a cross-sectional study in health-care workers to report evidence of pericarditis and myocarditis after SARS-CoV-2 infection. Methods We studied 139 health-care workers with confirmed past SARS-CoV-2 infection (103 diagnosed by RT-PCR and 36 by serology). Participants underwent clinical assessment, electrocardiography, laboratory tests including immune cell profiling and cardiac magnetic resonance (CMR) imaging.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 32 publications
(32 reference statements)
4
71
0
Order By: Relevance
“…References classified into the cardiovascular and hematological category included two prospective cohort studies, one cross-sectional study and one case report [ [25] , [26] , [27] , [28] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…References classified into the cardiovascular and hematological category included two prospective cohort studies, one cross-sectional study and one case report [ [25] , [26] , [27] , [28] ].…”
Section: Resultsmentioning
confidence: 99%
“…Time to follow-up examination varied from 11 days after quarantine to approximatively three months post-diagnosis. Three studies performed cardiac magnetic resonance imaging and observed evidence of peri-, myoperi- and myocarditis in 3-26% of the participants [ [25] , [26] , [27] ]. One study showed altered immune cell counts 9-11 weeks after symptom onset [ 25 ], while a case report described isolated thrombocytopenia in a patient approximatively one month after symptom onset [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preprint, also looking at health-care workers >2 months after disease resolution suggested rates of myocarditis, myopericarditis, and pericarditis at 26%, 11% and 4% respectively. Both studies relied on cardiac MRI and hsTnT for these diagnoses [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies have shown that myocardial injury is encounted more often than it was thought and about 40% of patients with COVID-19, not only critically ill, had increased troponine values (14). Cardiac magnetic resonance studies demonstrated that 78% of patients after recovery from COVID-19 had signs of inflammation and myocardial oedema (15) or develop asymptomatic myopericarditis late after disease (16). Autopsy studies showed presence of virus genome in myocardium (17).…”
mentioning
confidence: 99%